A focused ion beam sample preparation method based on a micro-nano material sample and use thereof

CN123008408APending Publication Date: 2026-10-30EAST CHINA NORMAL UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611233228.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

现阶段该尺度颗粒仅能沿用传统滴样法,将颗粒滴涂于载网后选取边缘薄区观测,存在有效观测区域狭小、样品厚度分布不均等问题,既无法精准解析颗粒内部微观结构,还易因厚度差异导致成像聚焦困难、成像质量不佳,难以满足高精度透射电子显微技术表征的需求

Benefits of technology

[0023]本发明填补了微纳米级颗粒透射电镜专用制样的技术空白,突破了现有制样技术的尺度断层。当前常规滴样法仅适用于100 nm以下超细颗粒,传统FIB制样仅适配尺寸在几十微米以上的块体材料,针对微纳米尺度离散颗粒无成熟制样工艺。本发明通过固相工艺制备粒径均匀、结构稳定的微纳米级离散颗粒,结合导电剂与粘结剂复合体系,将离散无加工基体的微纳米颗粒固化为整体性良好的铝箔块体结构,有效解决了该尺度颗粒无法直接进行FIB剖切减薄的技术难题,实现了微纳米级颗粒材料的稳定、可控制样。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123008408A_ABST
    Figure CN123008408A_ABST
Patent Text Reader

Abstract

The application discloses a kind of based on micro-nanoparticle material sample's focused ion beam sample preparation method and use, belong to transmission electron microscope sample preparation technical field, comprising: selecting or preparing the micro-nanoparticle of size in micro-nanometer level;Through particle, conductive agent and binder compounding coating, drying roll pressing process, discrete particle is solidified into FIB processable aluminum foil matrix bulk sample;Rely on SEM-FIB double-beam system, through protective layer deposition, trench excavation, wafer transfer, gradient ion thinning and low-damage polishing, prepare the defect-free ultrathin sample with thickness in 20~100 nm;Combining spherical aberration correction transmission electron microscope realizes the global accurate characterization of micro-nanoparticle atomic level microstructure.The application fills the blank of micro-nanometer level discrete particle FIB sample preparation technology, avoids the distortion problem of traditional sample preparation structure, and the sample imaging is uniform, the sample preparation repeatability is good, the process stability is high, can be adapted to multiple micro-nanometer level particle characterization, and is suitable for energy storage, catalysis, optoelectronic and other material fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of focused ion beam preparation for transmission electron microscopy observation, specifically involving focused ion beam (FIB) sample preparation of micro and nanomaterials, including preparation before ion beam cutting of micro and nanomaterials, ion beam sample preparation process, and transmission electron microscopy characterization of samples. Background Technology

[0002] With the rapid iterative development of nanomaterials and micro / nano device technologies, transmission electron microscopy (TEM), with its ultra-high spatial resolution and precise micro-area analysis capabilities, has become a core characterization tool for resolving the morphology, crystal structure, interface features, and microscopic defects of nanomaterials. TEM relies on an electron beam penetrating the sample to complete signal imaging, placing stringent requirements on ultra-thin sample thickness. The quality of sample preparation directly determines the accuracy and reliability of the transmission characterization results, and is a crucial prerequisite for the microstructural analysis of nanomaterials.

[0003] Existing transmission electron microscopy (TEM) sample preparation techniques mainly include the drop method, ultrathin sectioning method, mechanical grinding method, electropolishing method, conventional ion thinning method, and focused ion beam (FIB) sample preparation method. Each of these techniques has inherent technical limitations and applicability restrictions. The drop method is only suitable for extremely small-diameter nanoparticles and ultrathin two-dimensional materials, limiting its application scenarios. The ultrathin sectioning method is mostly used for biological and organic low-hardness materials, requiring the introduction of an embedding medium, making the process cumbersome and demanding extremely high sample chemical stability, thus unsuitable for inorganic hard nanomaterials. Traditional bulk sample preparation techniques such as mechanical grinding, electropolishing, and conventional ion thinning suffer from strong randomness in material sampling and the inability to target specific micro-regions. Furthermore, mechanical forces easily induce plastic deformation, surface scratches, and stress-induced pseudo-defects, severely masking the intrinsic microstructure of the material and significantly reducing characterization accuracy.

[0004] Focused ion beam (FIB) sample preparation is currently the mainstream transmission electron microscopy (TEM) technique for bulk materials. Utilizing a dual-beam electron microscope, it enables precise visualization and fabrication of micro-areas. Through high-energy ion beam sputtering etching, it achieves targeted cutting, thinning, and deposition modification of samples, effectively addressing the limitations of traditional sample preparation techniques, such as the inability to target materials and severe mechanical damage. This technique allows for nanoscale precision sample preparation, producing samples with uniform thin areas, large effective observation areas, and high fidelity in microstructure. It is widely applicable to various solid materials, including metals, ceramics, semiconductors, composite materials, and multilayer heterostructures, and is suitable for high-precision transmission characterization of complex microstructures, precision micro / nano devices, and rare, trace samples.

[0005] Existing standardized FIB sample preparation processes are mature: the target observation area of ​​the sample is located through electron beam scanning imaging, a 1-3 μm thick metal protective layer is deposited on the surface of the area, symmetrical trenches 10-15 μm deep are excavated on both sides of the protective layer using a high-current ion beam, and micron-sized thin sheet samples are obtained by peeling. The thin sheet is then transferred and fixed to a grid using a nano-manipulator, and after fine thinning and polishing with an ion beam, a qualified transmission electron microscope sample with a thickness of 20-100 nm is obtained. As can be seen from the sample preparation process, this process has significant application limitations; the entire processing system is designed for bulk samples with dimensions of at least tens of micrometers. This method has certain requirements on sample size and cannot currently be directly used for transmission electron microscopy sample preparation of micro / nano-scale discrete particles.

[0006] Currently, there is a significant technological gap in the field of transmission electron microscopy (TEM) sample preparation for micro and nanoparticles: nanoparticles with a diameter of less than 100 nm can be prepared and observed using the drop method, while bulk nanomaterials of tens of micrometers and larger can be processed using conventional ion thinning or FIB bulk sample preparation processes. However, for micro and nanoparticle materials at the micro-nano scale, there is no mature and dedicated sample preparation technology in the industry. At present, particles at this scale can only be observed using the traditional drop method, where particles are dropped onto a grid and then observed in a thin area at the edge. This method suffers from problems such as a small effective observation area and uneven sample thickness distribution. It cannot accurately resolve the internal microstructure of the particles and is prone to difficulties in focusing the image due to thickness differences, resulting in poor image quality, which is difficult to meet the requirements of high-precision TEM characterization. In summary, to address the gaps and deficiencies in existing sample preparation technologies, it is urgent to develop a dedicated TEM sample preparation method adapted to micro and nanoparticle materials to fill the technical gap in sample preparation for this scale. Summary of the Invention

[0007] To address the deficiencies and gaps in existing technologies, the purpose of this invention is to provide a focused ion beam sample preparation method and its applications based on micro / nanomaterial samples. This invention uses micro / nano-sized particles as a typical research object. The overall sample preparation process first selects or prepares discrete micro / nano-sized particles with controllable particle size. Then, the discrete micro / nano-sized particles are bonded and solidified using a binder and conductive agent system to construct a sample with an integral bulk structure. Finally, the solidified discrete particle sample is subjected to precise focused ion beam thinning to achieve high-quality transmission electron microscopy characterization of the micro / nano-sized particles.

[0008] The specific technical solution for achieving the objective of this invention is as follows:

[0009] A focused ion beam sample preparation method based on micro / nanomaterial samples includes the following steps:

[0010] Step 1: Selection of micro / nanoparticles or preparation

[0011] Micro- and nano-particles with a particle size between 10 μm and 100 nm are selected or prepared, and the micro- and nano-particles have crystallinity, chemical stability and dispersibility;

[0012] Step 2: Solidify micro / nanoparticles into aluminum foil-based bulk samples

[0013] Micro-nanoparticles, conductive agents, and binders were mixed in a mass ratio of 8:1:1, and an organic solvent was added to obtain a uniform and stable slurry. The slurry was coated onto the surface of an aluminum foil carrier, and then vacuum dried, rolled to densify, and cut into sheets to prepare an aluminum foil sheet with uniformly embedded micro-nanoparticles and a dense and stable structure. This process solidifies and molds the discrete micro-nanoparticles, forming a bulk sample that can be processed by focused ion beam. The conductive agent is carbon black; the binder is polyvinylidene fluoride; and the organic solvent is analytical grade N-methylpyrrolidone.

[0014] Step 3: Focused ion beam preparation of samples suitable for transmission electron microscopy observation

[0015] The SEM-FIB dual-beam system was used to perform electron beam localization imaging on the target micro-area of ​​aluminum foil. The process involved sequentially depositing a carbon / tungsten double protective layer, excavating bilateral symmetrical trenches, non-destructive picking of micron-level thin sheets and fixing of the carrier, multi-gradient ion beam thinning, and ion polishing at a voltage below 5kV. This resulted in the preparation of a transmission sample with an effective observation area thickness of 20–100 nm, free from sputtering damage and amorphous layers.

[0016] Furthermore, the micro / nanoparticles mentioned in step 1 are purchased or prepared, and can be of any composition.

[0017] Furthermore, in step 2, the vacuum drying is carried out at a temperature of 40~120 ℃ for a drying time of 8~16 h; the rolling process compacts the thickness of the dried aluminum foil to 80% of the initial thickness, thereby improving the density and uniformity of the structure.

[0018] Furthermore, the carbon / tungsten double protective layer described in step 3 has a carbon protective layer thickness of 1~3 μm, a width of 1~4 μm, and a length of 2~25 μm, and a tungsten protective layer thickness of 1~3 μm, a width of 1~4 μm, and a length of 2~25 μm; the trench excavation has a depth of 5~30 μm.

[0019] Furthermore, step 3, the multi-gradient ion beam thinning and ion polishing at a voltage below 5 kV, includes: initially using a large beam current of 30 kV and 0.79 nA to thin the sample to a thickness of 400-1000 nm; switching to a medium beam current of 30 kV and 80 pA to continue thinning; finally using a small beam current of 5 kV and 40 pA to thin the sample to 20-100 nm; and after thinning, using a beam current of 2 kV and 20 pA to perform ion polishing on the thin area of ​​the sample.

[0020] A transmission sample prepared based on the above method.

[0021] One application of the above-mentioned transmission sample is for microstructure characterization. The transmission sample is subjected to spherical aberration-corrected transmission electron microscopy high-resolution imaging test to offset imaging spherical aberration, realize clear focusing of micro and nanoparticles from the edge to the interior, and accurately characterize particle lattice structure, lattice distortion, micro defects and interface structure features.

[0022] Beneficial effects of the present invention

[0023] This invention fills the technological gap in dedicated sample preparation for transmission electron microscopy (TEM) of micro- and nano-sized particles, overcoming the scale limitations of existing sample preparation technologies. Currently, conventional droplet methods are only suitable for ultrafine particles smaller than 100 nm, and traditional FIB sample preparation is only applicable to bulk materials with sizes larger than tens of micrometers. There is no mature sample preparation process for micro- and nano-sized discrete particles. This invention prepares uniformly sized and structurally stable micro- and nano-sized discrete particles through a solid-state process. Combined with a conductive agent and binder composite system, the discrete micro- and nano-sized particles without a processed matrix are solidified into a well-integrated aluminum foil bulk structure. This effectively solves the technical challenge of directly performing FIB slicing and thinning of particles at this scale, achieving stable and controllable samples of micro- and nano-sized particle materials.

[0024] This invention overcomes the inherent defects of traditional drop sampling methods for preparing micro- and nano-scale particulate materials, significantly improving the accuracy of microscopic characterization. Traditional drop sampling methods can only observe naturally thin regions at the particle edges, resulting in limited effective observation areas, uneven thickness, and difficulties in imaging focusing. They cannot resolve the true internal microstructure of the particles, leading to extremely poor repeatability and accuracy. This invention, relying on SEM-FIB dual-beam visualization and point-based processing technology, can accurately obtain the complete ultrathin cross-section of the target particle. The thickness of the thin region is uniform and controllable, enabling the true reconstruction of the particle's internal lattice structure, defect configuration, and interface characteristics, fundamentally ensuring the authenticity and reliability of the characterization results.

[0025] The sample preparation method of this invention features low sample damage, high versatility, and high application value. The entire sample preparation process involves no external mechanical force, avoiding artificial defects such as plastic deformation and stress distortion caused by mechanical grinding. Combined with metal protective layer deposition and low-voltage ion polishing, it effectively suppresses ion implantation and surface amorphization issues, preserving the intrinsic structure of the material to the greatest extent. Furthermore, the process of this invention is standardized and highly reproducible, and its application scope can be extended to multi-element modified energy storage micro / nano materials and other particulate materials with sizes in the micro / nano range. It is widely adaptable to the microscopic characterization needs of multiple fields such as energy storage, catalysis, and optoelectronics, and possesses excellent prospects for scientific research and engineering applications. Attached Figure Description

[0026] Figure 1 This shows the preparation of Li by solid-state method. 1.2 Ni 0.2 Mn0.6 XRD pattern of O2 micro / nano particles;

[0027] Figure 2 This shows the preparation of Li by solid-state method. 1.2 Ni 0.2 Mn 0.6 SEM image of O2 micro / nanoparticles;

[0028] Figure 3 This diagram shows a low-magnification HAADF and internal atomic image of micron-sized particles after FIB sample preparation in Example 1 of the present invention.

[0029] Figure 4 This diagram shows a schematic image of HAADF atoms in the sample after FIB preparation in Example 2 of the present invention.

[0030] Figure 5 The TEM image and HAADF atomic image of the sample prepared by the drop method in Comparative Example 1 of the present invention are shown. Detailed Implementation

[0031] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. Although the description of the present invention is presented in conjunction with preferred embodiments, this does not mean that the features of the invention are limited to these embodiments. On the contrary, the invention is described in conjunction with embodiments to cover other options or modifications that may be derived based on the claims of the present invention. To provide a deep understanding of the invention, many specific details will be included in the following description. The invention may also be implemented without these details. Furthermore, to avoid confusion or obscuring the focus of the invention, some specific details will be omitted in the description. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of the present invention can be combined with each other.

[0032] This invention discloses a transmission electron microscopy (TEM) focused ion beam (FIB) sample preparation method adapted to micro / nano-scale particles. The core principle is as follows: select or prepare particles with micro / nano-scale dimensions, then use a conductive agent and binder system to solidify the discrete particles into a bulk aluminum foil sample. Finally, use a SEM-FIB dual-beam system to achieve point-to-point micro-area thinning to prepare a sample suitable for TEM observation. Specific examples of micro / nano-scale particles will be used to illustrate this method.

[0033] A focused ion beam sample preparation method based on micro / nanomaterial samples according to the present invention includes the following steps:

[0034] Step 1: Selection or preparation of micro / nanoparticles

[0035] Micro- and nano-particles with a particle size between 10 μm and 100 nm are selected or prepared, and the micro- and nano-particles have crystallinity, chemical stability and dispersibility;

[0036] The micro / nanoparticles can be of any composition and can be purchased if selected; the preparation process specifically includes:

[0037] 1. Preparation of micro / nanoparticles

[0038] This step employs a solid-state sintering process to prepare discrete particles with micro- and nano-sized particle sizes. By precisely stoichiometrically proportioning the stoichiometric particles, high-energy ball milling for homogeneous dispersion, and segmented high-temperature calcination to control grain growth, highly crystallizable, uniformly sized, and structurally stable micro- and nano-sized particle materials can be obtained, providing a qualified substrate for subsequent electrode fabrication and micro-area sample preparation. Specifically, the steps include the following:

[0039] 1-1. Raw material ratio: The raw materials with a purity of 99.9% are selected, and the components of each raw material are precisely proportioned in strict accordance with the stoichiometric ratio; in order to compensate for the high-temperature volatilization loss of elements during the high-temperature calcination process, additional loss elements are added on the basis of the standard stoichiometric ratio.

[0040] 1-2. Ball milling dispersion: Place all the prepared raw materials in an ethanol dispersion medium and disperse them using a planetary ball mill at a speed of 100~300 rpm for 1~4 hours to ensure that the solid raw materials are fully mixed and uniformly dispersed, eliminate the agglomeration of raw materials, and ensure the uniformity of the precursor components.

[0041] 1-3. Constant temperature drying: After ball milling, collect the mixed slurry and place it in a constant temperature drying device. Dry it continuously at 40~60 ℃ to completely remove the ethanol solvent and obtain a dry, loose, homogeneous precursor powder.

[0042] 1-4. Segmented high-temperature calcination: The dried precursor powder is loaded into an alumina crucible and a segmented temperature-controlled calcination process is adopted. First, the temperature is raised to 500 ℃ and pre-calcined at a constant temperature for 5 h to complete the thermal decomposition, impurity removal and preliminary nucleation of the precursor. Then, the temperature is raised to 900 ℃ at a uniform heating rate of 5 ℃ / min and calcined for 20 h to ensure that the material is fully crystallized. After cooling to room temperature, micro-nano particle materials with complete crystals and uniform particle size are obtained.

[0043] 2. Micro-nano particles solidified into aluminum foil substrate samples

[0044] This step involves preparing a composite slurry with the prepared micro / nanoparticles, conductive agents, and binders. This slurry is then combined with coating, vacuum drying, and roll-pressing densification processes to create a uniformly structured and stable aluminum foil. This allows the micro / nanoparticles to be uniformly embedded within the system, achieving the solidification and bonding of the discrete nanoparticles. This forms a bulk sample suitable for focused ion beam (FIB) slicing and micro-area extraction, solving the problem that single micro / nanoparticles cannot be directly used for FIB sample preparation. Specifically, the steps include:

[0045] 2-1. Material mixing: The micro-nano particles, conductive carbon black, and binder polyvinylidene fluoride (PVDF) prepared in step 1 are precisely weighed according to a certain mass ratio and uniformly mixed to obtain composite particulate material.

[0046] 2-2. Slurry preparation: Add an appropriate amount of N-methylpyrrolidone (NMP) organic solvent to the mixed particles in portions, and fully mix the particles and solvent by ball milling to prepare a stable slurry with uniform flowability, no agglomeration and no precipitation.

[0047] 2-3. Coating and forming: Select smooth aluminum foil as a carrier, and use a doctor blade coating process to evenly coat the prepared slurry onto the smooth surface of the aluminum foil to ensure that the slurry coating thickness is uniform and the coverage surface is flat.

[0048] 2-4. Vacuum drying: Place the coated aluminum foil in a vacuum drying oven and set the drying temperature to 80 ℃. Bake in a constant temperature vacuum for 8~16 h to completely remove the residual NMP solvent and trace moisture inside the aluminum foil, and avoid solvent residue affecting the stability of the electrode structure.

[0049] 2-5. Rolling densification: After the aluminum foil has completely cooled to room temperature, measure the initial thickness of the aluminum foil and record the data; use a rolling press to compact the dried aluminum foil, and precisely roll the aluminum foil thickness to 80% of the initial thickness, effectively improving the compaction density and overall structural uniformity of the aluminum foil.

[0050] 2-6. Cutting and preparing the aluminum foil: The roll-formed complete aluminum foil sheets are cut into regular pieces. At the same time, the cut aluminum foil samples are weighed and the parameters are recorded. Aluminum foil sheets with complete structure and uniform thickness are selected for use.

[0051] 3. Focused ion beam preparation of samples suitable for transmission electron microscopy observation.

[0052] This step utilizes a SEM-FIB dual-beam system to perform visualized, targeted micro-area processing on bonded and cured micro / nano-scale particle aluminum foil. Through a gradient processing approach involving micro-area positioning, surface protection, trench excavation, sheet transfer, fine thinning, and ion polishing, multiple micro / nano-scale particles are simultaneously prepared non-destructively and ultra-thinly. This effectively solves the technical challenges of limited observation area, uneven thickness, and inability to characterize the internal structure of particles inherent in traditional droplet methods, significantly improving the accuracy of micro / nano-scale particle microstructure characterization. Specifically, the steps include:

[0053] 3-1 Sample clamping and positioning: The aluminum foil to be tested prepared in step 2 is stably fixed on the sample stage of the SEM-FIB dual-beam system. The sample angle and focal length are adjusted, and electron beam scanning imaging is turned on to observe the micro morphology of the aluminum foil surface in real time. The micro-nano particles, particle interfaces and micro-feature regions to be tested are accurately located to complete the positioning of the target micro-area.

[0054] 3-2. Surface Protective Layer Deposition: The gas injection system of the equipment is activated to deposit a dense carbon and tungsten protective layer on the surface of the target observation micro-area after positioning. This layer isolates the sample from high-energy ion bombardment during subsequent ion etching, effectively preventing amorphization, ion implantation, and microstructural damage to the sample surface and protecting the intrinsic structure of the sample.

[0055] 3-3. High-current trench excavation: Switch to a high-current focused ion beam and precisely excavate trenches of uniform depth at symmetrical positions on both sides of the protective layer. Quickly and efficiently remove redundant matrix material around the target micro-area and separate a micron-scale sheet structure containing multiple micro- and nano-scale particles to be tested.

[0056] 3-4. Non-destructive transfer and fixation of thin films: The built-in nanomanipulator of the dual-beam system is used to non-destructively pick up and precisely transfer the micron-sized thin films that have been peeled off, and fix the thin films stably on the TEM special grid, ensuring that the thin films are free from displacement, wrinkles and structural damage.

[0057] 3-5. Refined Ion Thinning: Switch to a high-precision ion beam with a small beam current and low acceleration voltage to perform progressive, uniform, and refined etching thinning on both sides of the fixed thin sheet, gradually adjusting the thickness of the effective observation area of ​​the sample to the electron beam transmission adaptation range of 20-100nm.

[0058] 3-6. Low-damage ion polishing: After thinning, the thin area of ​​the sample is subjected to low-voltage ion polishing to completely remove the surface sputtering damage layer and amorphous layer generated during the ion etching process. Finally, a high-quality transmission electron microscope sample with complete structure, uniform thickness, clean surface and no artificial defects is obtained, which meets the requirements of subsequent high-precision microstructure characterization and testing.

[0059] 4. Aberration-corrected transmission electron microscopy observation of samples after FIB preparation: The atomic-level microstructure of the ultrathin samples prepared above was characterized using aberration-corrected transmission electron microscopy.

[0060] Example 1

[0061] Step 1: Li 1.2 Ni 0.2 Mn 0.6 Preparation of O2 micro / nanoparticles

[0062] 1-1: Lithium hydroxide monohydrate (LiOH·H2O, Aladdin) with a purity of 99.9%, nickel hydroxide (Ni(OH)2, Aladdin) with a purity of 99.9%, and manganese hydroxide (Mn(OH)2, Ningbo Gauss New Energy Technology Co., Ltd.) were selected as raw materials for preparation, strictly following the Li 1.2 Ni 0.2 Mn 0.6 The stoichiometric ratio of each raw material component in O2 (hereinafter referred to as LNMO) is precisely measured;

[0063] 1-2: Place all the prepared raw materials in an ethanol dispersion medium and disperse them by ball milling at 200 rpm for 2 hours using a planetary ball mill to ensure that the solid raw materials are fully mixed and uniformly dispersed.

[0064] 1-3: After ball milling, collect the mixed slurry and place it in a constant temperature drying oven. Dry it at 50 ℃ for 5 h to completely remove the ethanol solvent and obtain a dry, loose, homogeneous precursor powder.

[0065] 1-4: The dried precursor powder was packed into an alumina crucible and subjected to a segmented temperature-controlled calcination process: First, it was heated to 500 °C at a heating rate of 5 °C / min and pre-calcined at this temperature for 5 h to complete the thermal decomposition, impurity removal, and preliminary nucleation of the precursor; then, it was heated to 900 °C at a uniform heating rate of 5 °C / min and calcined at this temperature for 20 h to obtain LNMO micro / nano particle materials with complete crystals and uniform particle size. Figure 1 and Figure 2 The images shown are the XRD and scanning electron microscope (SEM) images of the samples.

[0066] Step 2: Solidify micro / nanoparticles into aluminum foil-based bulk samples

[0067] The LNMO micro-nanoparticles prepared in step 1 are mixed with conductive agents and binders to form a composite slurry. The slurry is then combined with coating, vacuum drying and roll densification processes to prepare aluminum foil with uniform structure and good stability. This allows the micro-nanoparticles to be uniformly embedded in the system, achieving the curing and bonding of discrete micro-nanoparticles.

[0068] 2-1: The LNMO micro / nanoparticles, conductive carbon black, and binder polyvinylidene fluoride (PVDF) prepared in step 1 are precisely weighed in a mass ratio of 8:1:1 and uniformly mixed to obtain composite particulate material.

[0069] 2-2: Add an appropriate amount of N-methylpyrrolidone (NMP) organic solvent to the mixed particles in portions, and fully mix the particles and solvent by ball milling to prepare a stable slurry with uniform flowability, no agglomeration and no precipitation.

[0070] 2-3: Using a smooth aluminum foil as a carrier, the prepared electrode paste is uniformly coated onto the smooth surface of the aluminum foil using a doctor blade coating process to ensure uniform paste coating thickness and a smooth coverage surface.

[0071] 2-4: Place the coated aluminum foil sheet stably in a vacuum drying oven, set the drying temperature to 80 ℃, and bake it under constant temperature vacuum for 12 h to completely remove the residual NMP solvent and trace moisture inside the aluminum foil sheet, so as to avoid the solvent residue affecting the structural stability.

[0072] 2-5: After the aluminum foil has completely cooled to room temperature, measure the initial thickness of the aluminum foil and record the data; use a rolling mill to compact the dried aluminum foil, and precisely roll the aluminum foil thickness to 80% of the initial thickness, effectively improving the compaction density and overall structural uniformity of the aluminum foil;

[0073] 2-6: The roll-formed complete aluminum foil sheets are cut into regular pieces. At the same time, the cut aluminum foil samples are weighed and the parameters are recorded. Aluminum foil sheets with complete structure and uniform thickness are selected for use.

[0074] Step 3: Focused ion beam preparation of samples suitable for transmission electron microscopy observation

[0075] 3-1: Fix the aluminum foil to be tested prepared in step 2 onto the sample stage of the dual-beam system, adjust the sample angle and focal length, turn on electron beam scanning imaging, observe the micro morphology of the aluminum foil surface, and find the area with good sample density and high flatness.

[0076] 3-2: A protective layer is deposited on the selected area surface using a gas injection system. First, a carbon layer with a thickness of 1 μm, a width of 2 μm, and a length of 8 μm is deposited. Then, a tungsten protective layer with a thickness of 2 μm, a width of 2 μm, and a length of 8 μm is deposited by changing the gas source.

[0077] 3-3: Dig symmetrical trenches with a depth of 10 μm on both sides of the deposited protective layer location, remove redundant matrix material around the target micro-region, and peel off to obtain micron-sized sheets containing target particles;

[0078] 3-4: Manipulate the nanorobotic arm to fix the peeled micron sheet onto a TEM-specific grid;

[0079] 3-5: Adjust the ion beam current to 0.79 nA and the accelerating voltage to 30 kV to reduce the thickness of the fixed sheet; when the thickness is around 600 nm, switch the beam current to 80 pA and keep the accelerating voltage at 30 kV to further reduce the sheet thickness; as the thickness decreases further, switch the beam current to 40 pA and the accelerating voltage to 5 kV to reduce the thickness to below 100 nm.

[0080] 3-6: The thinned slices were polished using a beam current of 20 pA and an accelerating voltage of 5 kV to remove the surface sputtering damage layer and amorphous layer generated during the ion etching process, resulting in a high-quality transmission electron microscope sample with complete structure, uniform thickness, and clean surface.

[0081] Step 4: Aberration-corrected transmission electron microscopy observation of samples after FIB preparation.

[0082] The ultrathin samples prepared above were characterized at the atomic level, and high-resolution imaging tests were carried out using aberration-corrected transmission electron microscopy.

[0083] like Figure 3 As shown in Figure a, after the micro / nanoparticles are bonded and solidified before FIB sample preparation, the morphology and size of the sample particles do not change. After solidification, the particles are relatively tightly packed together. FIB sample preparation not only yields samples suitable for transmission electron microscopy observation but also allows for the extraction of multiple particles, thereby increasing the range of selectable particles for characterization. Atomic diagram of the sample ( Figure 3 As can be seen in b), FIB sample preparation yields a clear atomic image of the sample, with clear focusing from the sample edge to the sample interior simultaneously. This proves that the method of this invention can successfully solve the problem of preparing micro / nano-scale particles for transmission electron microscopy.

[0084] Example 2

[0085] Step 1: Na 0.8 Li 0.26 Mn 0.74 Preparation of O2 micro / nanoparticles

[0086] Na 0.8 Li 0.26 Mn 0.74O2 was prepared via a solid-state reaction using Na2CO3 (99.5%, 2% excess), Li2CO3 (99.5%, 2% excess), and MnO2 (99.95%) as raw materials. These raw materials were uniformly mixed with anhydrous ethanol by ball milling at 200 rpm for 2 hours. After drying and pressing into tablets, the precursor was calcined in air in a muffle furnace at 750 °C for 15 hours at a heating rate of 2 °C / min, and then cooled to 300 °C at a cooling rate of 2 °C / min.

[0087] Steps 2, 3, and 4 in this embodiment are the same as in embodiment 1.

[0088] After replacing the nanoparticles with components different from those in Example 1, the method provided by this invention can obtain a clear atomic structure inside the sample, from which the atomic migration inside the sample can be clearly observed. Figure 4 As shown in a, in addition, it is possible to focus simultaneously from the edge to the interior of the sample, as shown in Figure a. Figure 4 As shown in b in the figure. Therefore, this method can ensure that atomic images of the sample edge and interior can be focused simultaneously, and the internal information of sample particles can be accurately analyzed by transmission electron microscopy.

[0089] Example 3

[0090] Steps 1, 2, and 4 in this embodiment are the same as in embodiment 1.

[0091] Step 3: Focused ion beam preparation of samples suitable for transmission electron microscopy observation

[0092] 3-1: Fix the aluminum foil to be tested prepared in step 2 onto the sample stage of the dual-beam system, adjust the sample angle and focal length, turn on electron beam scanning imaging, observe the micro morphology of the aluminum foil surface, and find the area with good sample density and high flatness.

[0093] 3-2: A protective layer is deposited on the selected area surface using a gas injection system. First, a carbon layer with a thickness of 2 μm, a width of 4 μm, and a length of 25 μm is deposited. Then, a tungsten protective layer with a thickness of 2 μm, a width of 4 μm, and a length of 25 μm is deposited by changing the gas source.

[0094] 3-3: Dig symmetrical trenches with a depth of 30 μm on both sides of the location of the deposited protective layer, remove redundant matrix material around the target micro-region, and peel off to obtain micron-sized sheets containing target particles;

[0095] 3-4: Manipulate the nanorobotic arm to fix the peeled micron sheet onto a TEM-specific grid;

[0096] 3-5: Adjust the ion beam current to 0.79 nA and the accelerating voltage to 30 kV to reduce the thickness of the fixed sheet; when the thickness is around 400 nm, switch the beam current to 80 pA and keep the accelerating voltage at 30 kV to further reduce the sheet thickness; as the thickness decreases further, switch the beam current to 40 pA and the accelerating voltage to 5 kV to reduce the thickness to below 100 nm.

[0097] 3-6: The thinned slices were polished using a beam current of 20 pA and an accelerating voltage of 5 kV to remove the surface sputtering damage layer and amorphous layer generated during the ion etching process, resulting in a high-quality transmission electron microscope sample with complete structure, uniform thickness, and clean surface.

[0098] Comparative Example 1

[0099] Using the traditional drop method, steps 1 and 4 in this example are the same as in Example 1.

[0100] Step 2: Disperse the prepared LNMO micro / nanoparticles in ethanol solvent at a certain ratio and sonicate for 10 min to obtain a uniformly dispersed suspension.

[0101] Step 3: Drop the evenly dispersed suspension onto a transmission electron microscope (TEM) grid, bake it with an infrared lamp to allow the ethanol to evaporate completely, and then dry it to obtain a sample that can be observed under a TEM.

[0102] The aberration-corrected transmission electron microscopy characterization results of the sample prepared by the drop method in Comparative Example 1 are as follows: Figure 5 As shown, Figure 5 The 'a' in the figure shows the size of the particle, which is approximately at the micro-nano scale. The atomic image of this particle is shown in the figure. Figure 5 In b), the edge atomic structure is clear, while the internal atomic structure gradually becomes blurred. This indicates that the sample prepared by the drop method cannot be focused simultaneously due to the uneven sample thickness, and the internal structure is relatively thick, making it difficult to analyze the internal structure information of the particles.

[0103] While the present invention has been illustrated and described with reference to certain preferred embodiments, those skilled in the art should understand that the above description is a further detailed explanation of the invention in conjunction with specific embodiments, and should not be construed as limiting the specific implementation of the invention to these descriptions. Various changes in form and detail can be made by those skilled in the art, including several simple deductions or substitutions, without departing from the spirit and scope of the invention.

Claims

1. A focused ion beam sample preparation method based on micro / nanomaterial samples, characterized in that, Includes the following steps: Step 1: Selection of micro / nanoparticles or preparation Micro- and nano-particles with a particle size between 10 μm and 100 nm are selected or prepared, and the micro- and nano-particles have crystallinity, chemical stability and dispersibility; Step 2: Solidify micro / nanoparticles into aluminum foil-based bulk samples Micro-nanoparticles, conductive agents, and binders were mixed in a mass ratio of 8:1:1, and an organic solvent was added to obtain a uniform and stable slurry. The slurry was coated onto the surface of an aluminum foil carrier, and then vacuum dried, rolled to densify, and cut into sheets to prepare an aluminum foil sheet with uniformly embedded micro-nanoparticles and a dense and stable structure. This process solidifies and molds the discrete micro-nanoparticles, forming a bulk sample that can be processed by focused ion beam. The conductive agent is carbon black; the binder is polyvinylidene fluoride; and the organic solvent is analytical grade N-methylpyrrolidone. Step 3: Focused ion beam preparation of samples suitable for transmission electron microscopy observation The SEM-FIB dual-beam system was used to perform electron beam localization imaging on the target micro-area of ​​aluminum foil. The process involved sequentially depositing a carbon / tungsten double protective layer, excavating bilateral symmetrical trenches, non-destructive picking of micron-level thin sheets and fixing of the carrier, multi-gradient ion beam thinning, and ion polishing at a voltage below 5kV. This resulted in the preparation of a transmission sample with an effective observation area thickness of 20–100 nm, free from sputtering damage and amorphous layers.

2. The focused ion beam sample preparation method according to claim 1, characterized in that, The micro / nanoparticles mentioned in step 1 are purchased or prepared and can be of any composition.

3. The focused ion beam sample preparation method according to claim 1, characterized in that, The vacuum drying in step 2 is carried out at a temperature of 40~120 ℃ for 8~16 h; the rolling process compacts the thickness of the dried aluminum foil to 80% of the initial thickness, thereby improving the density and uniformity of the structure.

4. The focused ion beam sample preparation method according to claim 1, characterized in that, The carbon / tungsten double protective layer described in step 3 has a carbon protective layer thickness of 1~3 μm, a width of 1~4 μm, and a length of 2~25 μm, and a tungsten protective layer thickness of 1~3 μm, a width of 1~4 μm, and a length of 2~25 μm; the trench excavation has a depth of 5~30 μm.

5. The focused ion beam sample preparation method according to claim 1, characterized in that, Step 3, the multi-gradient ion beam thinning and ion polishing at a voltage below 5 kV, includes: initially using a large beam current of 30 kV and 0.79 nA to thin the sample to a thickness of 400~1000 nm; switching to a medium beam current of 30 kV and 80 pA to continue thinning; finally using a small beam current of 5 kV and 40 pA to thin the sample to 20~100 nm; after thinning, using a beam current of 2 kV and 20 pA to perform ion polishing on the thin area of ​​the sample.

6. A transmission sample prepared by the method of claim 1.

7. The use of the transmission sample according to claim 6, characterized in that, Used for microstructure characterization.

8. The use according to claim 7, characterized in that, The transmission sample was subjected to high-resolution transmission electron microscopy with spherical aberration correction to counteract imaging spherical aberration, achieving clear focusing of micro and nanoparticles from the edge to the interior, and accurately characterizing the particle lattice structure, lattice distortion, microscopic defects and interface structure features.